The Influence of Educational Games and Learning Management on the Learning Motivation of Kindergarten Students in Malang City - Hutabarat, Indah Annisa Sena; Sunarni, Sunarni; Sultoni, Sultoni; Arifin, Imron (Universitas Negeri Malang, 2024)
The research objectives are to determine: 1) the level of educational games; 2) level of learning management; 3) level of learning motivation; 4) the influence of educational games on student learning motivation, 5) the influence of learning management on student learning motivation, 6) the influence of educational games and learning management on student learning motivation. This research is research that uses quantitative methods. The population of this study was kindergarten students throughout Malang City with a sample size of 206 respondents. The research results illustrate: 1) The level of educational games is included in the high category; 2) The level of learning management is included in the high category; 3) The level of student learning motivation is in the high category; 4) There is a significant positive influence of educational games on student learning motivation with a correlation coefficient value of 0.736, which is included in the strong category; 5) There is a significant positive influence of learning management on student learning motivation with a correlation coefficient value of 0.831, which is in the very strong category; and (6) There is a positive and significant influence together between education games and learning management on student learning motivation. Keywords: education games; learning management; learning motivation